Inventory Management Automation - Barnawi; Athar, Daffa Aurellia (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Inventory management automation is a modern solution in inventory management that leverages technology to enhance efficiency, accuracy, and transparency in goods management. By implementing automated systems such as cloud-based inventory management software, barcode technology, and IoT (Internet of Things), processes such as counting, monitoring, and tracking stock become easier and real[1]time. This automation reduces human errors, accelerates decision-making, and enables stock demand forecasting based on historical data analysis. Additionally, integration with other systems like ERP (Enterprise Resource Planning) ensures a seamless flow of information between departments. This article discusses the benefits, challenges of implementation, and the positive impact of inventory management automation on company productivity. Proper implementation can help companies optimize resources, reduce operational costs, and enhance customer satisfaction through more responsive services.